(3GdedNU aj GdLOds - (3EHQGgje Hf Ydj Hf jhSa GdTjQGRj GdajQhRGHGOj , CHh ESMGb , LeGd GdOjf,J (B476 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf deG QCjJ GdfXQ Cbhi WQjb jOQc Hg GdYde OYJfi faSi Edi dNjU cJGH edNU ai GdLOd s
(3BNQgG (B:s
(3aUd , hddEfbWGY YdGeGJ, aefgG SchJ GdMjQI ef ZjQ YPQ hdG YGQV agPG cdg jYQa Hg YLRg hEfbWGYg YeG dReJg fUQJg eeG bOefGg s
(3GdfSNI HgG MhGTs
(3Ydi MhGTjgG HYV GdJUMjMGJs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B51 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B68s
Keywords: (3Gdabg GdESdGejs